Rekomendasi Pemberian Kredit Pemilikan Rumah (KPR) Pada Nasabah Bank Menggunakan Metode AHP - Topsis (Studi Kasus: PT. Bank Negara Indonesia. Tbk) - Andriko Hedi Prasetyo; Imam Cholissodin; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
One of the important things that need or become a primary human need is a place to live or home. Many people can directly buy by credit. In this case the bank provides services for individuals who want to have a place to live or a decent house. This bank can be used as a financial institution that can ease the burden of the payment process to be able to make a home loan. In this study took a case study at PT. Bank Negara Indonesia (BNI) in the recommendation of granting KPR. With the increasingly brilliant Home Ownership Credit (KPR) program, every agency that provides a KPR program is demanded to be quick and precise in completing the families who apply for a KPR. So it requires time efficiency, accuracy of results in selecting mortgage customers and to improve the quality and service of the bank. Analytic Hierarchy Process Method - Order Preference Technique by Ideal Solution (AHP - TOPSIS) was chosen at the time of research because the AHP method has advantages in a different process from one another. And the TOPSIS method has advantages in practical decision making and the results of alternative decisions. The results of this study provide subreferences at 5 values that produce a value of Î»max = 5.3351 CI = 0.0838 and CR = 0.0748 which get 85% accuracy results from 40 test data.